A Comparison of Collection Methods for Microbial Volatiles - Rering, Caitlin C.; Gaffke, Alexander M.; Rudolph, Arthur B.; Beck, John J.; Alborn, Hans T. (Frontiers in Sustainable Food Systems, 2020)
Recently, there has been an increase in the number of reports that highlight the role of microbes and their volatile metabolites in interactions with plants and insects, including interactions which may benefit agricultural production. Accurate and reproducible volatile collection is crucial to investigations of chemical-mediated communication between organisms. Accordingly, accurate detection of volatiles emitted from microbe-inoculated media is a research priority. Though numerous classes of volatile organic compounds are emitted from plants, insects, and microbes, emissions from microbes typically contain polar compounds of high volatility. Therefore, commonly used plant or insect volatile collection techniques may not provide an accurate representation of microbe-specific volatile profiles. Here, we present and compare the volatile data derived via three solventless collection techniques: direct headspace injection, solid-phase microextraction (SPME), and active sampling with a sorptive matrix blend specifically designed to prevent collection filter breakthrough of VOCs (solid-phase extraction, SPE). These methods were applied to a synthetic floral nectar media containing a nectar-inhabiting yeast, Metschnikowia reukaufii, and sunflower (Helianthus annus) pollen. The yeast contributed alcohols, ketones, and esters, and the pollen provided terpenoids. Direct headspace injections were not effective, and the resultant chromatography was poor despite the use of on-column cryofocusing. SPME and SPE detected a similar number of volatiles, but with varying relative abundances. SPE collected a greater abundance of microbial volatiles than SPME, a difference driven by high ethanol capture in SPE. Both SPE and SPME are appropriate for analysis of microbial volatiles, though the sorbent type and amount, and other collection parameters should be further evaluated for each studied system.